Prosthetic solution for whistling in fixed prostheses on implants: a case report (Research, Society and Development, 2022)
This clinical case report aims to describe the prosthetic solutions in a case of phonetic alteration reported by the patient after multiple anterosuperior rehabilitation with seven single cemented crowns type FP2, responsible for the lispting, reversing the prosthetic rehabilitation in four FP3 splinted and screwed crowns with palatal flange. Initially, the patient was unsatisfied with an upper removable partial denture. After the planning and execution of the surgical phase with eight osseointegrated implants, the osseointegration period occurred with the installation of seven single cemented crowns classified as FP2. During the adaptation period, the patient reported rattling during speech due to the passage of air in the cervical interdental region of the implant-supported prostheses (ISP), corresponding to teeth elements 22 to 12. When identifying the crowns responsible for the rattling, we elaborated a new plan with a FP3 splinted and screwed to guarantee reversibility, plus artificial cervical gum in the palatal region, called flange, replacing the lost anatomical crown and soft tissues. Several factors can result in phonetic changes; in the presented case, the multiple upper anterior prosthetic rehabilitation associated with the existence of a pronounced ogival palate and a thin gingival profile of the patient resulted in the development of whistling. The prosthetic conversion of crowns from FP2 to FP3 with palatal flange ensuring air locking between the cervical region of the FP proved satisfactory in resolving the condition of phonetic alteration, rehabilitating the lost phonemes.